Rancangan Draft Instrumen Pengkajian Cageur Stroke Skor dalam Mempersiapkan Keluarga Sebagai Caregiver Pasien - Ristonilassius Ristonilassius; Budiman Budiman; Susilawati Susilawati; Elly Nurachmah; Nandang A. Waluya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to explore families' experiences as caregivers regarding how to care for stroke patients at home and to design a concept assessment model for caregivers in caring for patients at home. The method used is qualitative research with a phenomenological approach. The results of the study on the experiences of 16 family members as caregivers were summarized into four research themes, namely: control of risk factors that cause stroke by caregivers, changes in behavior and emotions of stroke patients and caregiver responses, strategies to improve self-care for stroke patients at home by caregivers, and strategies to increase muscle strength. The patient is at home with a caregiver. The draft instrument for the Cageur Stroke Score assessment is still a draft concept that needs to be developed in subsequent research. The images are risk factors for stroke, control of risk factors for stroke, amok, caregiver response, personal hygiene, skin integrity, and muscle strength. In conclusion, the family's experience as caregivers regarding how to care for stroke patients at home is the result of observing what nurses do while the patient is in hospital, and they are not ready to continue post-stroke care at home. The conceptual design of the assessment model for caregivers in caring for patients at home will be developed from research concept themes. Keywords: Cageur Stroke Score, Family Caregiver, Stroke Care